Pengaruh Citra Perusahaan (Corporate Image) terhadap Loyalitas Nasabah dengan Kepuasan Nasabah sebagai Variabel Intervening pada Bank Syariah Indonesia (BSI) Kantor Cabang Pembantu Binjai Sudirman - Ridha Afrilia; Annio Indah Lestari; Arnida Wahyuni (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Customer loyalty is an absolute guide for banks to ensure survival in their business, because customer loyalty is the pinnacle of achievement in the banking business. By getting loyal customers, banks are able to create great opportunities to expand their marketing network and maintain the viability of the company. This study aims to determine the effect of corporate image on customer loyalty with customer satisfaction as an intervening variable. This study uses quantitative methods and associative approaches, data collection techniques using questionnaires. The population and sample consisted of 98 customers at BSI KCP Sudirman Binjai using the Side Purposive technique. Data were analyzed by simple linear regression and intervening methods. The results of this study indicate that the Corporate Image Variable has an effect on Customer Loyalty and the Customer Satisfaction Variable is able to strengthen the influence of Corporate Image on Customer Loyalty.